Interorganizational Information Sharing: Collaboration during Cybersecurity Threats - Solansky, Stephanie T.; Beck, Tammy (Public administration quarterly, 2021)
Information sharing is examined to determine if the willingness to share information relates to the willingness to collaborate in interorganizational actions used to address cybersecurity threats. This study employs ANOVA by placing 85 organizational representatives that participated in a cyber terrorism training exercise into two categories: higher versus lower willingness to share information. The dependent measures in this study are proxies for collaboration measured by willingness to seek assistance from other organizations and willingness to offer assistance to other organizations. There is a significant statistical difference between the two categorizations of organizational representatives. The category that had a lower tendency to share information also had a lower willingness to collaborate with other organizations. This research shows that sharing information is critical when collaborative interorganizational action is required to face cybersecurity threats. Managers of organizations that respond to cybersecurity threats should promote the tendency to share information with other organizations that have the resources to aid in addressing the threat. Organizations involved in cybersecurity threats that are willing to share information are more willing to participate in integrative interorganizational efforts. This study includes a sample of actual decision makers of organizations that would handle cybersecurity attacks in their community. In this study, we demonstrate the role of information sharing for enhancing integrative, collaborative action in a time where promoting this type of action is imperative to cybersecurity initiatives.